2018
DOI: 10.7150/thno.22514
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive monitoring of in vivo hydrogel degradation and cartilage regeneration by multiparametric MR imaging

Abstract: Numerous biodegradable hydrogels for cartilage regeneration have been widely used in the field of tissue engineering. However, to non-invasively monitor hydrogel degradation and efficiently evaluate cartilage restoration in situ is still challenging.Methods: A ultrasmall superparamagnetic iron oxide (USPIO)-labeled cellulose nanocrystal (CNC)/silk fibroin (SF)-blended hydrogel system was developed to monitor hydrogel degradation during cartilage regeneration. The physicochemical characterization and biocompati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 52 publications
1
64
0
Order By: Relevance
“…The articular cartilage is primarily composed of chondrocytes and extracellular matrix (ECM) that mainly contains water, collagen type II, and proteoglycans such as aggrecan 3 - 5 . When articular cartilage suffers focal or degenerative lesions caused by trauma or disorders, it has a limited capacity for self-healing because of its avascularity and low cellularity and ultimately could evolve into osteoarthritis (OA) that in turn could result in the degradation of articular hyaline cartilage and subchondral bone structural remodeling 6 - 12 . Thus, it is extremely significant to repair osteochondral defects and acquire new cartilage and bone tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The articular cartilage is primarily composed of chondrocytes and extracellular matrix (ECM) that mainly contains water, collagen type II, and proteoglycans such as aggrecan 3 - 5 . When articular cartilage suffers focal or degenerative lesions caused by trauma or disorders, it has a limited capacity for self-healing because of its avascularity and low cellularity and ultimately could evolve into osteoarthritis (OA) that in turn could result in the degradation of articular hyaline cartilage and subchondral bone structural remodeling 6 - 12 . Thus, it is extremely significant to repair osteochondral defects and acquire new cartilage and bone tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Hence the position changes of the fluorescence of USPIO can be used to monitor degradation of scaffold in real time (Lei et al, 2017). Previous research also reported that T2-weighted MRI imaging was stable and reasonable, USPIO-labeled scaffcan be monitored in real time (Chen et al, 2018).…”
Section: Mrimentioning
confidence: 99%
“…Apart from TiO 2 , iron oxide nanoparticles have been applied in cartilage and subchondral bone tissue engineering. The treatment of MSCs and chondrocytes with iron oxide nanoparticles on scaffolds increased the osteogenic and chondrogenesis differentiation, and the nanoparticles in conjunction with magnetic field exposure enhanced osteogenic differentiation and provided a new perspective on image‐guided osteochondral regeneration (Z. Chen, Yan, & Yan, ; M. O. Kim, Jung, Kim, Park, & Seo, ). Although the modification of metal oxides increased the mechanical and biological properties of the scaffolds, most of the metal oxides are nondegradable.…”
Section: Nanobased Scaffold Construction and Modificationmentioning
confidence: 99%